TRAINING OF BEDRIDDEN PATIENT CARE AND PRESSURE INJURY WOUND CARE AT HOME: PELATIHAN MERAWAT PASIEN TIRAH BARING DAN PERAWATAN LUKA TEKAN DI RUMAH - Chayati, Nur; Waliyanti, Ema; Betsyeba, Betsyeba; Anggraini, Maulida; Kusuma, Rahmah Yanita (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: The elderly population in Gunung Kidul Regency is steadily increasing each year, with many becoming bedridden as they age. This highlights the urgent need for training programs that empower family members caring for elderly relatives, particularly in bedridden care and pressure ulcer prevention. Objective: The training aims to enhance the understanding, attitudes, and skills of family caregivers to provide effective support for bedridden elderly patients. Method: The program featured interactive lectures, engaging discussions, and hands-on practice, along with pre-tests and post-tests to evaluate its effectiveness. Results: Analysis indicated a significant improvement in knowledge and attitudes, with a paired t-test value (p) of 0.000 (p<0.05). While participants actively engaged in practical exercises, some occasionally needed reminders about the correct order of steps. Conclusion: This training successfully improved participants' capabilities and confidence in caring for bedridden elderly individuals, ultimately enhancing the quality of care for this vulnerable population.